The Impact of Technology-Based Self-Service on User Satisfaction in Indonesia's National Library Self-Lending - Azizah, Anjella; Wanastri, Prisinta (Librarianship in Muslim Societies, 2024)
This study aims to determine the effect of technology-based self-service implementation on user satisfaction in the self-lending service at the National Library of the Republic of Indonesia using the Expectancy Disconfirmation Theory (EDT) model. The method used is explanatory quantitative research with 100 respondents who have used the self-lending platform machine at the National Library of the Republic of Indonesia. Measurement of research variables to determine the value of technology-based self-service Implementation and library satisfaction using a Likert scale. The data collection technique used was a survey, with data analysis through simple linear regression. The results showed that implementing technology-based self-service at the National Library of the Republic of Indonesia was classified as good, with a variable mean value of 3.35, which fell into the very high category (3.25-4.00). In addition, user satisfaction with implementing technology-based self-service is also very high, with an average value of 3.36, which means it falls into the very satisfied category. This study also found that the relationship between technology-based self-service and library satisfaction is relatively strong, with a Pearson correlation value of 0.461. The results indicate that the application of technology-based self-service significantly influences library satisfaction at the National Library of the Republic of Indonesia. Still, the influence is not dominant, with an influence value of 21.2%. Therefore, further research should be conducted to evaluate other factors affecting library satisfaction at the National Library of the Republic of Indonesia.